2020
DOI: 10.1002/edn3.169
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA typing of environmental RNA (eRNA): A case study on zebrafish tank water with perspectives for the future development of eRNA analysis on aquatic vertebrates

Abstract: As an alternative/supplement to conventional biodiversity survey methods, environmental DNA (eDNA) analysis has developed rapidly during the past decade, and is widely used for the biomonitoring of wildlife. However, the interpretation of eDNA results has been limited to the presence/absence or biomass/abundance of the target species because of uncertainty regarding the dynamics of eDNA in natural environments. This limitation may be ameliorated by targeting environmental RNA (eRNA). RNA is more prone to degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 48 publications
2
61
0
Order By: Relevance
“…For Daphnia , the mRNA-cDNA of the Chk1 gene regulates oocyte maturation during reproduction 53 and Caspase-3 mRNA increases with aging related to the appearance of sexual reproduction 54 . Recent studies have indicated advances in these techniques by demonstrating that eRNA can be detected from water 55 and sediment core samples 56 . Furthermore, it has been shown by using sedimentary mRNA that some zooplankton were surviving in dormancy in sediments and possibly use cytochrome c oxidase (COX) to exit dormancy 56 .…”
Section: Discussionmentioning
confidence: 99%
“…For Daphnia , the mRNA-cDNA of the Chk1 gene regulates oocyte maturation during reproduction 53 and Caspase-3 mRNA increases with aging related to the appearance of sexual reproduction 54 . Recent studies have indicated advances in these techniques by demonstrating that eRNA can be detected from water 55 and sediment core samples 56 . Furthermore, it has been shown by using sedimentary mRNA that some zooplankton were surviving in dormancy in sediments and possibly use cytochrome c oxidase (COX) to exit dormancy 56 .…”
Section: Discussionmentioning
confidence: 99%
“…To explain the mechanism underlying the findings in this study, future empirical research on the production source and persistence state of eDNA is required. For instance, detecting tissue-specific messenger RNA in water could identify the production source of eDNA (Tsuri et al, 2021). Alternatively, visualization of eDNA particles via fluorescence in situ hybridization (FISH) techniques and immunostaining (e.g., Kogure et al, 2006;Amann & Fuchs, 2008) may directly offer information on its cellular and the molecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent methodological developments to collect and extract environmental RNA (eRNA) might also be leveraged to understand changes of gene expression with physical and biological pressure (functional genomics; Tsuri et al, 2021), with possibilities of expansion into ecological epigenetics, ecosystem health, func-tional metagenomics, population-level inference, or even the interface of species-species interactions (e.g., Stewart & Taylor, 2020;Veilleux et al, 2021). Unlike eDNA, eRNA can go beyond species and PAI quantification, such as understanding life histories, ages, metabolic activities, physiological conditions and health of interacting organisms.…”
Section: Future Perspectivesmentioning
confidence: 99%